A multi-study examination of the relevance of the metacognitive beliefs about uncontrollability in emotion regulation and clinical symptoms - Salguero-Noguera, José Martín; Ramos-Cejudo, Juan (Elsevier, 2023)
Transdiagnostic approaches to psychopathology have postulated that factors related to perceived control are particularly relevant to mental health. Here we focused on a specific perceived control-related construct: metacognitive beliefs about uncontrollability. Evidence suggests that dysfunctional metacognitive beliefs play a role in the activation and maintenance of maladaptive emotion regulation strategies and emotional distress. Metacognitive beliefs about the uncontrollability and danger of worry are the most strongly associated with psychopathology. In this multi-study research, we hypothesized that metacognitive beliefs about uncontrollability make a specific contribution to emotion regulation strategies and clinical symptoms. We tested our hypotheses in four different studies, both cross-sectionally and longitudinally (N = 2224). Participants completed measures of metacognitive beliefs, maladaptive strategies (e.g., worry, thought suppression), and clinical symptoms (e.g., generalized anxiety, emotional distress, depressive and anxiety symptoms). Our results showed that uncontrollability beliefs were the strongest variable associated with maladaptive emotion regulation strategies and clinical symptoms (cross-sectionally), and the only ones that predicted them in the long term. We discuss the theoretical and clinical implications of these results in the light of the metacognitive model and control-related theories.
Keywords: Psicopatología; Trastornos afectivos; Emociones; Perceived control; Metacognitive beliefs; Emotion regulation; Emotional disorders; Trastornos emocionales; Autocontrol; Metaconocimiento